2017
DOI: 10.3758/s13414-017-1368-8
|View full text |Cite
|
Sign up to set email alerts
|

Visual training improves perceptual grouping based on basic stimulus features

Abstract: Training on visual tasks improves performance on basic and higher order visual capacities. Such improvement has been linked to changes in connectivity among mediating neurons. We investigated whether training effects occur for perceptual grouping. It was hypothesized that repeated engagement of integration mechanisms would enhance grouping processes. Thirty-six participants underwent 15 sessions of training on a visual discrimination task that required perceptual grouping. Participants viewed 20 × 20 arrays of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…Consistent with the familiarity of the letter stimuli driving this rapid perception of the configuration (grouping) of these line fragments, this priming effect emerged later for line fragments in an unfamiliar, inverted (180 degree rotated) letter configuration (Kimchi & Hadad, 2002 ). Lab-based training emphasising stimulus integration has also been shown to facilitate perceptual grouping (Kurylo et al, 2017 ). Therefore, rather than experience and perceptual grouping making independent contributions to supporting holistic processing of stimuli, experience may serve to bolster perceptual grouping within objects of expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the familiarity of the letter stimuli driving this rapid perception of the configuration (grouping) of these line fragments, this priming effect emerged later for line fragments in an unfamiliar, inverted (180 degree rotated) letter configuration (Kimchi & Hadad, 2002 ). Lab-based training emphasising stimulus integration has also been shown to facilitate perceptual grouping (Kurylo et al, 2017 ). Therefore, rather than experience and perceptual grouping making independent contributions to supporting holistic processing of stimuli, experience may serve to bolster perceptual grouping within objects of expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated significant and meaningful fine motor skills training benefits for both children and adults with ID (Azar, McKeen, Carr, Sutherland, & Horton, 2016;Sood, Ahmad, & Chavan, 2017). Visual perception skills can also be trained (Kurylo, Waxman, Kidron, & Silverstein, 2017). Especially effective and promising are computer-based games or programs aimed at improving children's perceptual and attention skills (Boot, Kramer, Simons, Fabiani, & Gratton, 2008;Green, Gorman, & Bavelier, 2016;Gozli, Bavelier, & Pratt, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, differences due to age and cognitive impairment in the global/local visual processing, as well as in the processing of other complex visual stimuli that require holistic processing 10.3389/fnagi.2022.893818 such as faces (Tanaka and Gordon, 2011;Kurylo et al, 2017;Gerlach and Poirel, 2018;Gerlach and Starrfelt, 2018), define a developing line of research for their potential to differentiate between healthy older adults and those with AD, including the prodromal stage of the disease that constitutes MCI. In sum, assessing global/local visual processing along with other cognitive processes such as visual memory, executive functions, and language could allow us to establish possible markers of cognitive impairment and possible progression to Alzheimer's dementia.…”
Section: Limitations Of the Present Study And Further Directions Of R...mentioning
confidence: 99%